Activity-Based Costing and Its Derivatives and Significance in the Cutting-Edge Environment - Tito IM. Rahman Hakim (Universitas Airlangga, 2018)
The purpose of this article is to explore activity-based costing with its derivative, that is time-driven activity-based costing and fuzzy time-driven activity-based costing via some relevant researches and observe significance of this systems in sophisticated business environment. Activity-based costing is a costing system with two phases that track cost from activity to product. The emergence of activity-based costing is driven by irrelevance calculation of traditional costing system that cause information distortion. Therefore, activity-based costing emerges as a alternative problem solving of this distortion. But activity-based costing as a system has its drawbacks. These drawbacks try to be covered later with the emergence of model development of former activity-based costing. Through time-driven activity-based costing, activity-based costing that previously complex and expensive become simpler and more economic. Subsequently, through uzzy time-driven activity-based costing, calculation of time-driven activity-based costing that previously in-absolute and ambiguity become less. Through three tradeoff analysis, that is cost-benefit, complexity-simplify, and first-secondary, it is known that activity-based costing and its derivative still have a great significance in business environment that full of sophistication and recency.